2020
DOI: 10.3390/ma13102417
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Fretting Wear Behavior and Damage Mechanism in Alloy 690TT with Cycle Number

Abstract: The evolution of fretting wear behavior and damage mechanism in Alloy 690TT with cycle number was investigated via laser scanning confocal microscopy (LSCM), scanning electron microscopy (SEM), focus ion beam (FIB), and transmission electron microscopy (TEM). The results showed that the fretting running status underwent a transition from partial slip and mixed stick-slip to final gross slip with the transformation of Ft–D curves from the ellipse to the parallelogram. The coefficient of friction (COF) experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…However, with extended service life, the fretting corrosion behavior between steam generator tubes and their support plates, caused by the combined action of flow-induced vibration and medium erosion, will cause significant damage to their outer surface (Cheng and Zuo, 2018). According to the statistics of service status statistics, the fretting corrosion in steam generator tubes is highly prevalent, unavoidable and has become the primary damage pattern in steam generator tubes (Xing, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, with extended service life, the fretting corrosion behavior between steam generator tubes and their support plates, caused by the combined action of flow-induced vibration and medium erosion, will cause significant damage to their outer surface (Cheng and Zuo, 2018). According to the statistics of service status statistics, the fretting corrosion in steam generator tubes is highly prevalent, unavoidable and has become the primary damage pattern in steam generator tubes (Xing, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oxidized debris will isolate the direct contact of the contact surface and cause serious underground damage. Xin et al [18][19] investigated the influence of frequency on the fretting corrosion behavior of the type 304 stainless steel and its mechanism under high temperature and high pressure water. Their results showed that the main sources of wear are delamination wear, material transfer wear, and oxidative wear.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [ 24 ] discussed the fretting running behavior and damage mechanisms of Cu–Mg alloy in different fretting regions in detail. Xin et al [ 25 ] investigated the evolution of fretting wear behavior and damage mechanism in Alloy 690TT. Duan et al [ 26 ] identified the role of nitrides (converted carbides) in fretting wear characteristics through the fretting experiments of the X210CrW12 steel against GCr15 steel ball.…”
Section: Introductionmentioning
confidence: 99%